Charter of the City of New Haven Page 142-143 (1881) §18 - (:unkn) unknown (General Publisher, 1881)
Prohibited the sale of any fixed ammunition, gun, pistol, or other mechnical contrivance arranged for the explosion of cartridge, or any fulminate to any child under the age of sixteen.
--
Keywords: TRANSFER - MINORS